Longitudinal study of ICET-A on glucose tolerance, insulin sensitivity and β-cell secretion in eleven β-thalassemia major patients with mild iron overload: Low serum ferritin and glucose homeostasis in β-thalassemia major - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Tzoulis, Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Background: Iron chelation therapy (ICT) is the gold standard for treating patients with iron overload, though its long-term effects are still under evaluation. According to current recommendations regarding  transfusion-dependent  (TD)  β-thalassemia major (β-TM) patients, their serum ferritin (SF) levels should be maintained below 1,000 ng/mL and ICT should be discontinued when the levels are